Self-Endowment as a Human Capital Instrument in Encouraging Islamic Economic Development in Islamic Boarding Schools - Maulana Zakaria Ahmad; Fauzan Fauzan; M.F Hidayatullah (LPPM STIES BABUSSALAM, 2026)
The practice of waqf in Islamic boarding schools (pesantren) has not only been manifested in the form of material assets but has also developed into self-waqf through the dedication of students' time, energy, and expertise. Self-waqf is a potential instrument for supporting human capital development from the perspective of Islamic economic development. However, studies examining the contribution of self-waqf to human resource development and pesantren-based Islamic economic development remain limited. This study aims to analyze the role of self-waqf in human capital development and its contribution to Islamic economic development within pesantren communities. The research employs a qualitative approach using a library research method through the analysis of relevant journals, books, and scientific publications. The findings indicate that self-waqf plays a significant role in shaping human capital through the development of skills, leadership, managerial experience, as well as the strengthening of spiritual and social values. Furthermore, self-waqf supports the sustainability of the pesantren economic ecosystem by creating productive, independent, and socially oriented human resources. Therefore, self-waqf can be considered a strategic instrument in promoting sustainable Islamic economic development based on pesantren institutions